Diaphragmatic paralysis in young children: A literature review. Issue 9 (18th June 2019) - Gerard‐Castaing, Nathalie; Perrin, Thomas; Ohlmann, Camille; Mainguy, Catherine; Coutier, Laurianne; Buchs, Clelia; Reix, Philippe
Abstract: Diaphragmatic paralysis (DP) is a rare cause of respiratory distress in young children. In the first years of life, the main cause is phrenic nerve injury after cardiothoracic surgery or obstetrical trauma. DP usually presents as respiratory distress. Asymmetrical thorax elevation, difficulty weaning from mechanical ventilation, pulmonary atelectasis, and repeated pulmonary infections are other suggestive signs or complications. DP is usually suspected on chest X‐ray showing abnormal hemidiaphragm elevation. Although fluoroscopy was considered the gold standard for DP confirmation, it has gradually been replaced by ultrasound, which can be done at the bedside. Some electrophysiological tools may be useful for a better characterization of phrenic nerve injury and chance of recovery. The management of DP is mainly based on clinical severity. In mild asymptomatic cases, DP may only require close monitoring. In more severe cases, adequate ventilatory support and/or surgical diaphragmatic plication may be needed. Electrophysiological tools may help clinicians assess the ideal timing for diaphragmatic plication.